2011
DOI: 10.4236/jdm.2011.14015
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow increases human islets insulin positive cells in co-culture: quantification with flow cytometry

Abstract: We have previously demonstrated that allogeneic human bone marrow (BM) supports human islet function and longevity in vitro. We hypothesize that BM supporting human islets may include to increase β-cell in cultured islets. In this study, we developed a method to quantify insulin-producing β cells from cultured islets by using immunofluorescent staining and flow cytometry analysis to explore this possibility. The results show that human islets cocultured with BM for 39 days contained a significantly higher numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…In our study, bone marrow cells blocked the initiation of cell apoptosis by inhibiting P2X7R activation, protecting human islet β-cell from apoptosis ( Figure 6 ). Furthermore, islet function in terms of insulin release was maintained in comparison with the deterioration occurred in islet only group ( Figure 5A ), which is consistent with our previous studies [ 38 ]. The correlation of insulin and IL-1β release demonstrated that the reduction of insulin concentration might be related with the increasing release of IL-1β in islet only cultures, while BM co-culture prevented the increase in IL-1β.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, bone marrow cells blocked the initiation of cell apoptosis by inhibiting P2X7R activation, protecting human islet β-cell from apoptosis ( Figure 6 ). Furthermore, islet function in terms of insulin release was maintained in comparison with the deterioration occurred in islet only group ( Figure 5A ), which is consistent with our previous studies [ 38 ]. The correlation of insulin and IL-1β release demonstrated that the reduction of insulin concentration might be related with the increasing release of IL-1β in islet only cultures, while BM co-culture prevented the increase in IL-1β.…”
Section: Discussionsupporting
confidence: 92%